THERAPEUTIC CRISPR/CAS9 GENOME EDITING TOOL FOR TREATING SICKLE CELL DISEASE - MEHAR, A; GHAFFAR, M; MUSTAFA, S; IQBAL, S; MASOOD, B; SHAHID, I (Biological and Clinical Sciences Research Journal, 2024)
Sickle cell disease (SCD) is a serious inherited condition that leads to high rates of illness and mortality, and a complete cure is not yet available. Recent advances suggest that correcting the genetic mutations in hematopoietic stem/progenitor cells (HSPCs) or boosting fetal hemoglobin might stop red blood cells from sickling. Techniques like CRISPR/Cas9 genome editing and creating induced pluripotent stem cells (iPSCs) are being explored to address SCD more effectively. Genome editing has proved beneficial as a treatment choice. CRISPR/Cas9's ongoing revelations have disrupted genetic design and opened the possibility of the idea into an actual clinical reality. We summarize DNA designing software that uses CRISPR/Cas9, causing problems, and the future perspectives of CRISPR/Cas9 being a viable option to treat SCD. A genome-altering technology that is designed to treat SCD alteration of the β-globin's quality in non-hematopoietic hematopoietic cells, red blood cells, which make normal hemoglobin protein, is enhanced by this modification. Suppose a donor template that is homologous to the donor is codified. In that case, we demonstrate that the Transcription Activator-Like Effector Nucleases (TALENs), as well as the CRISPR/Cas9 nuclear cleavage system, could focus DNA sequences in the vicinity of the sickle-cell variant in the gene, allowing for specific site-cutting and facilitating accurate correction. Off-target and on-target cleavage rates for different pairs of TALENs and guide RNAs for CRISPR have been assessed. In vitro, the CRISPR/Cas9 proteins were introduced directly to CD34+ cells, which resulted in more than 18% gene modifications. Furthermore, we demonstrate how sickle cell disease mutation within CD34+ hematopoietic stems derived from bone marrow cells and trails cells from sickle cell disease patients triggers the production of wild-type hemoglobin. Findings suggest promising improvements in gene editing precision and potential treatment outcomes, though challenges still exist regarding off-target effects, delivery systems, and ethical considerations.